Strategi Penanganan Pembiayaan Bemasalah Pada Pembiayaan Murabahah Di Masa Pandemi Covid-19 - Azwar, Martavevi (Zhafir | Journal of Islamic Economics, Finance, and Banking, 2021)
As a sharia financial institution, the business activity of Bank Syariah Indonesia KC Daanmogot Tangerang is to collect public funds in the form of deposits and channel them back in the form of loans. In distributing financing, the financing that is most in demand by the public at Bank Syariah Indonesia KC Daanmogot Tangerang is murabahah financing. However, in providing financing to customers, it cannot be separated from various risks, one of which is non-performing financing, because it can lead to a decrease in the health level of bank liquidity and the level of trust of debtors to the bank. So that this study was conducted to examine the handling strategies carried out by banks against non-performing financing during the covid-19 pandemic. The main problem in this research is. first, what are the factors that cause problematic financing during the covid-19 pandemic, and second, how is the strategy for handling problematic financing in murabahah financing at Bank Syariah Indonesia KC Daanmogot Tangerang. The type of research used in this project is field research. Research that is taking the research location at Bank Syariah Indonesia Branch Office Daanmogot Tangerang with a qualitative approach. Sources of data in this study consisted of primary sources and secondary sources obtained through interviews and documentation. The data that has been collected is then analyzed using descriptive analysis method. From the results of this study concluded that the factors causing problematic financing during the COVID-19 pandemic can come from customers and Bank Syariah Indonesia Daanmogot Tangerang Branch Office. The strategy for handling problematic financing on murabahah financing during the Covid-19 pandemic at the Daanmgot Tangerang Branch Office, namely by, Approaching customers, Intensive collection, Giving warning letters, namely SP 1 to 3, and Restructuring by rescheduling, namely, extending the financing period, extending the installment period, and the most used during this covid-19 pandemic is reducing the number of installments.